Characterization and selective deposition of carbon nanotubes from carbon nanoparticles mixture using mild acid treatment and electrokinetic manipulation - Abdulhameed, Abdullah; Mohtar, Mohd Nazim; Hamidon, Mohd Nizar; Mansor, Ishak; Abdul Halin, Izhal (IOP Publishing, 2021)
Materials Research Express PAPER • THE FOLLOWING ARTICLE ISOPEN ACCESS Characterization and selective deposition of carbon nanotubes from carbon nanoparticles mixture using mild acid treatment and electrokinetic manipulation Abdullah Abdulhameed5,1,2, Mohd Nazim Mohtar2,3, Mohd Nizar Hamidon2,3, Ishak Mansor4 and Izhal Abdul Halin2